Green synthesis of zinc oxide nanoparticles using arabic gum and photocatalytic degradation of direct blue 129 dye under visible light - Taghavi Fardood, Saeid; Ramazani, Ali; Moradi, Sajjad; Azimzadeh Asiabi, Pegah (Journal of materials science. Materials in electronics, 2017)
In this work, zinc oxide (ZnO) nanoparticles were synthesized using arabic gum as a biotemplate source by the sol–gel method and its photocatalytic dye degradation ability from aqueous solution was studied. This method has many advantages such as nontoxic, economic viability, ease to scale up, less time consuming and environmental friendly approach for the synthesis of ZnO nanoparticles without using any organic chemicals. Direct blue 129 (DB129) was used as model dye. The synthesized ZnO nanoparticles were characterized by powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy, scanning electron microscopy and UV–Visible spectroscopy. The X-ray powder diffraction (XRD) analysis revealed the formation of wurtzite hexagonal phase ZnO with average crystallite size of 10 nm. Photocatalytic dye degradation by ZnO nanoparticles was studied using UV–Vis spectrophotometer. The effects of process parameters like, catalyst dosage, initial dye concentration, and visible light irradiation on dye degradation have been investigated.